The impact of internship experience and career aspirations on the academic performance of railway electrical automation students in China - Haojie, Liu; Taddese, Esayas Teshome; Yingying, Wang; Jiangping, Nan (Frontiers in Education, 2025)
This study examined the structural mechanisms through which internship experience and career aspirations influence academic performance among railway electrical automation students in China, grounded in Social Cognitive Career Theory (SCCT). Utilizing stratified multi-stage sampling (N = 403) and quantitative analyses (regression, mediation tests), three key findings emerged: (1) High-quality internships (duration ≥6 months, task relevance, technical depth) directly enhance academic performance (β = 0.218, p < 0.001), validating the theory-practice integration pathway; (2) Career aspirations, particularly realism (β = 0.107, p = 0.032), independently predict GPA, while clarity of goals shows a non-significant negative trend (β = −0.086, p = 0.096). Synergistic effects were observed in deep internships; (3) Career aspirations mediate 34.8% of internship effects (95% CI [0.078, 0.146]), revealing an indirect “internship →goal→academic” pathway. The study advances SCCT's dynamic “experience-goal” framework and proposes policy strategies for optimizing China's industry-education integration, including extended internships and regional resource rebalancing. Limitations include cross-sectional design and regional sample bias, necessitating longitudinal validation.